Effect of Low Temperature Preservation Without Cryoprotectant and Under Me2SO protection on the Activity of Reductive-Oxidative Enzymes in Placenta Tissue - Yurchenko, T. N.; Belonozhko, A. P.; Zhulikova, E. P.; Sharlaj, T. M. (Problems of Cryobiology and Cryomedicine, 2004)
Using the methods of quantitative histochemistry and quantitative photometric analysis there was carried-out the investigation of change in SDG, LDG, Î±-GPhDG, NAD.H2 and NADP.H2 activity in placenta tissue after its low temperature preservation without cryoprotectant and after treatment with Me2SO cryoprotectant solution.